Cancer Stem Cells: A Cause or A Consequence of Field Cancerization - Ninjit Dhanota; Sunil K Arora (International Journal of Translational Research, 2018)
A review discusses the relationship between cancer stem cells and field cancerization, considering bidirectional influences and implications for prevention and targeted therapy.
Keywords: Cancer Stem Cells